Dampak Game Free Fire Max terhadap Perilaku Agresi Komunikasi Verbal Anak TPQ di Masjid Baitul Hikmah Ajung Kabupaten Jember - Mohammad Taufik Romadhoni (Icon: Islamic Communication and Contemporary Media Studies, 2025)
Online games have become an integral part of children's lives, including in religious education environments. This study aims to analyze the impact of free fire max on verbal aggression in communication among TPQ (Taman Pendidikan Al-Qur’an) students at Masjid Baitul Hikmah, Dusun Penanggungan, Ajung District, Jember Regency. This research employs a qualitative descriptive approach using observation, interviews, and document analysis. The findings indicate that a high intensity of gaming correlates with increased verbal aggression, including the use of harsh language and raised voices in social interactions. Additionally, the study examines the role of religious teachers (ustadz) and parents in addressing the negative effects of gaming on children. The conclusion highlights the importance of supervision and educational programs to mitigate the negative impact of online games in TPQ environments.